Virtual Language Learning Finding Gems Amongst the Pebbles - Felix, Uschi; Monash Univ., Clayton, Victoria (Australia). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1998)
This document is intended for teachers and students who want to use the resources offered on the World Wide Web for second language instruction and learning. It assists in a comprehensive exploration of resources with different types of delivery, content, and level of interaction. The book is free of technical jargon, making insight into the complexity of the task all the easier for the user who is not technically-inclined. Resources include the following: comprehensive lists of URLs in a large number of languages, typically including a wide range of links; comprehensive lists of URLs for a single language, also extensively linked; and sites that focus on a single language. Selection of resources has focused on resources that have the potential to be integrated into existing courses; are instantly usable, in some cases without a teacher; are free or available at a reasonable cost; and are substantial and/or provide useful self-contained activities. Resources are not judged or rated by the author beyond the stated selection criteria; they are merely offered for the reader to pick and choose among. The book is divided into four parts: an introduction; annotated lists of example sites; making sense of the technology; and getting the language right--text input and output. Four appendices are included: useful sites for English-as-a-Second/Foreign-Language; selected links pages for languages in general and specific languages; on-line readings related to MUDs and MOOs; and sites included at the last minute that bear watching. (Contains 66 references.) (KFT)
Availability: Publications and Clearinghouse Manager, Language Australia Ltd., GPO Box 372F, Melbourne, VIC 3001, Australia.
Sponsoring Agency: Language Australia, Melbourne (Victoria).
ERIC Note: A CD-ROM accompanies the book.
Practitioners.
Students.
Teachers.
Keywords: Adult Education; Computer Assisted Instruction; Computer Mediated Communication; Computer Networks; Computer Uses in Education; Educational Resources; Elementary Secondary Education; Independent Study; Information Dissemination; Information Networks; Instructional Materials; Internet; Listservs; Second Language Instruction; Second Language Learning; World Wide Web; Guides, Non-Classroom.; Reference Materials, Bibliographies